The application of Metaphor in advertising discourses (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Metaphor frequently assumes a leading role in advertising language because it influences consumers' desires and emotions and motivates them to take action. Only the beneficial and essential qualities of the good or service, or its merits, are updated with its assistance, making it challenging for customers to assess them impartially. In this article, it is paid attention to advertising metaphorical models. metaphors are regarded as "a fast and powerful means to convey an idea," and in advertisements, they contribute to the following: the brightness of the advertising image; the recipient's ease of understanding of the advertisement; identification through stereotypes; and the speed of communication (short texts provide more information more quickly). Accordingly, a metaphor is described as a concealed comparison that is made by referring to one thing by name while exposing a significant aspect of the other.